The Employment Effects of Generous and Unconditional Cash Support - Timo Verlaat; Federico Todeschini; Xavier Ramos (Institute of Labor Economics (IZA), 2023)
While unconditional cash transfers have been studied extensively in developing countries, little is known about their effects in a wealthier context. Through a randomized controlled trial, we study the employment effects of a generous and unconditional transfer targeting low-income families in Spain. Two years into the program, subjects assigned to treatment are 20 percent less likely to work than subjects assigned to a control group. Assignment to an activation plan does not attenuate adverse effects; a more lenient transfer withdrawal rate does. It appears that effects are driven by subjects with children, suggesting substitution of labour for care tasks.
Keywords: C93; H53; I38; J64; 330; welfare reform; cash transfer; basic income; policy evaluation; RCT